Optimasi Prosedur Kultur H9C2 Kardiomioblas: Sebuah Pembelajaran untuk Membangun Model Studi In-vitro Kardiovaskular - Fadhillah, Muhamad Rizqy; Arozal, Wawaimuli; Wibowo, Heri (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2024)
Cardiovascular disease become one of the leading factors of death in the world. Thus, research is urgently needed to discover newer drugs or therapeutical agents and biological plausibility. The H9C2 cardiomyoblast originated from embryonic BDIX rat ventricular cells and was previously used in numerous in vitro studies because of its similar nature to cardiomyocytes. However, to our knowledge, there are still limited studies on the basic procedure for culturing H9C2 cardiomyoblast and arranging the best strategy to perform a suitable timeline. Here, we shared our experience in culturing the H9C2 cardiomyoblast, including harvesting and subculturing the cells. We also demonstrated the change of cell confluency, depending on the seeding number, serum concentration, and culture flask through days 1, 3, and 6, to determine their doubling-time population. H9C2 cardiomyoblasts’ doubling time is around 48-54 days with Mean±SD 2.38±0.41. However, seeding density, different culture flasks, and serum concentration have become independent factors in determining specific measures to harvest the cells for further experiments.